ANALISIS PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN - Setyaningrum, Dyah; Syafitri, Febriyani (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
The purpose of this research is to analyze the effect of local government characteristics on the level of disclosure of Local Government Financial Statements (LKPD) based on Government Accounting Standard. We use sample from 620 LKPD in Indonesia during 2008-2009. We found that the average rate of LKPD disclosure is 52.09%. The local government characteristics which are age, wealth and legislature size have significant positive effect on LKPD disclosure level, while intergovernmental revenues have significant negative effect. On the otherhand, government size, functional differentiation, work specialization, the ratio of financial independence and debt financing has no effect on LKPD disclosure level.